Kolaborasi antara Dinas Parawisata, RRI Sumba Barat dan Masyarakat Lokal Kecamatan Lamboya pada Pelaksanaan Ferstival Pasola di Sumba Barat - Melinda Kristiani Robaka; Veki Edizon Tuhana; Sandra Clarissa Umbu Datta (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the collaboration among the Tourism Office, RRI Sumba Barat, and local communities in supporting the promotion and preservation of the Pasola Festival in West Sumba Regency. The research employed a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings reveal that the success of the Pasola Festival is supported by collaborative efforts involving government institutions, mass media, and indigenous communities through a community-based participatory communication model. Indigenous leaders (Rato) serve as cultural authorities responsible for determining ritual implementation, while the Tourism Office acts as a facilitator and provider of official information. RRI Sumba Barat functions as a communication channel that disseminates information and promotes cultural education to both local communities and tourists. The collaboration is implemented through an integrated communication system, the utilization of digital media, cross-sector coordination, and community participation in festival promotion and supervision. The study demonstrates that synergy among stakeholders contributes to preserving the sacred values of Pasola while strengthening sustainable cultural tourism development. Therefore, collaborative communication plays a crucial role in maintaining the sustainability of local cultural heritage amid the growth of the tourism industry.